Wastewater treatment of biodiesel production using persulphate ion as an oxidant - Borralho, Teresa (2020)
The production of biodiesel produces a highly polluting effluent, because presents high values of Chemical Oxygen Demand (COD), oils and fats, among other contaminants. Sodium persulphate is a powerful oxidant (Eº = 2.1V). In addition to the direct oxidation that is favored in alkaline media, it can be induced by photolytic processes, catalytic and / or catalytic photos forming sulphate radicals (Eº = 2.6 V) thus providing reaction mechanisms with free radicals like hydroxyl radicals.